Термолюмінесцентні та дозиметричні характеристики тканино-еквівалентних люмінофорів - Ignatovych, M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
A comparative characterization of undoped lithium tetraborate (LTB) and Cu-doped (LTB:Cu) single crystals to commercially produced TLD-100 and TLD-700 dosimeters is reported. The result shows that LTB:Cu is approximately 50 times more sensitive to gamma-radiation than LTB and 5 times as compared to TLD-100 and TLD-700. At the same time LTB is 5 times more sensitive to thermal neutrons which suggests the application of paired LTB and LTB:Cu for mixed gamma-neutron field dosimetry.